Representation of Image Recognition For Attendance Validity Online: Representation of Image Recognition For Attendance Validity Online - Muhammad Haekal; Ucuk Darussalam; Novi Dian Nathasia (Jurnal Mantik, 2020)
Imageis a 2-dimensional intensity function f (x, y), where x and y are the spatial coordinates and f at the point (x, y) is the brightness of an image at a point. An image obtained from the capture of light reflected by the strength of the object. Output image as a recording apparatus, such as cameras, digital games can be analag, Figure itself was composed of pixels that can be taken into account. Thus the images suitable for use as a sample in this study. In this case the process of designing and manufacturing of online attendance system that is able to detect the validity of a student. The system uses the template matching method is used as a student face detection. Mathcing Template Method is a technique in digital image processing to find small parts of the image that matches the image of existing templates. The application will test the input image is detected or not. The results showed that the inputted face image detected correctly. Therefore, the study concluded that Macthing template method is suitable for use in the attendance system.